Multi-branch fusion graph neural network based on multi-head attention for childhood seizure detection - Li, Yang; Yang, Yang; Song, Shangling; Wang, Hongjun; Sun, Mengzhou; Liang, Xiaoyun; Zhao, Penghui; Wang, Baiyang; Wang, Na; Sun, Qiyue; Han, Zijuan (Frontiers in Physiology, 2024)
The most common manifestation of neurological disorders in children is the occurrence of epileptic seizures. In this study, we propose a multi-branch graph convolutional network (MGCNA) framework with a multi-head attention mechanism for detecting seizures in children. The MGCNA framework extracts effective and reliable features from high-dimensional data, particularly by exploring the relationships between EEG features and electrodes and considering the spatial and temporal dependencies in epileptic brains. This method incorporates three graph learning approaches to systematically assess the connectivity and synchronization of multi-channel EEG signals. The multi-branch graph convolutional network is employed to dynamically learn temporal correlations and spatial topological structures. Utilizing the multi-head attention mechanism to process multi-branch graph features further enhances the capability to handle local features.Experimental results demonstrate that the MGCNA exhibits superior performance on patientspecific and patient-independent experiments. Our end-to-end model for automatic detection of epileptic seizures could be employed to assist in clinical decision-making.